PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA CV KEMBAR JAYA PARUNG - Raffiyudin Al-Afgani Raffi; Henni Marlinah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
organizational culture on employee performance at CV Kembar Jaya Parung. The method used is a quantitative method. This data collection technique is carried out by taking objects from the sample which is called sampling or respondents, the sampling method uses a saturated sampling technique. The research sample was 75 respondents. Data analysis methods used in research include instrument tests consisting of validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, simple linear regression tests, correlation coefficients, coefficient of determination tests, hypothesis testing consisting of a partial t test and a simultaneous f test. From the results of this research it can be concluded that compensation has a positive and significant influence on employee performance with a t-label value of or (10.979 > 1.993) and a significance value of 0.000 < 0.050. Thus, H0 is rejected and H1 is accepted. Organizational culture has a positive and significant influence on employee performance with a t-label value or (11.431 > 1.993) and a significance value of 0.000 < 0.05. Thus, H0 is rejected and H2 is accepted. Compensation and organizational culture have a positive and significant influence on employee performance with a value of Fcount > Ftable or (80.684 > 3.120) and a significance value of 0.000 < 0.050. Thus, H0 is rejected and H3 is accepted. Compensation and organizational culture on employee performance have a regression effect of Y = 7.537 + 0.382 (X1) + 0.357 (X2). The result of the correlation coefficient value is 0.832, it can be concluded that the compensation variables (X1) and organizational culture (X2) together have an influential contribution to the employee performance variable (Y) of 69.1%, while the remaining 30.9% is influenced by other factors or variables not studied.